A detection method of the turned white belly fish based on improved SSD. Issue 1 (April 2021) - Tian, Ganglu; Li, Daoliang; Li, Wensheng; Zhang, Lu; Zhang, Hongxu; Duan, Qingling
Abstract: Aquaculture water pollution and fish disease caused the phenomenon of fish turning white belly. The accurate detection of the phenomenon of fish turning white belly was of great significance for emergency warning, reducing loss and improving the quality of aquatic products. There were few studies on the detection of the turned white belly fish in the fish swarm. The current research was mainly to identify single the turned white belly fish under a simple background, which was not applicable in the real aquaculture environment. In order to solve the above problems, a detection method of the white belly fish based on improved SSD was proposed in a complex environment. Crucian carp was taken as the experimental object and the proposed detection method of the turned white belly fish had been tested on the real dataset. The results showed that the average detection accuracy of white-bellied fish was 99.8%, and the average detection accuracy of normal fish was 98.8%, which was suitable for the complex environment with high breeding density and many interferences.